Molecular cloning of the cDNA for a mutant mouse ribonucleotide reductase M1 that produces a dominant mutator phenotype in mammalian cells. - Caras, I W (1988)
Mammalian ribonucleotide reductase is regulated by the binding of dATP and other nucleotide effectors to allosteric sites on subunit M1. Using mRNA from a mutant mouse T-lymphoma (S49) cell line, we have isolated a cDNA which encodes an altered, dATP feedback-resistant subunit M1. The mutant cDNA contains a single point mutation (a G-to-A transition) at codon 57, converting aspartic acid to asparagine. Proof that this mutation is responsible for the phenotype of dATP feedback resistance is provided by the following evidence. (i) The mutation was detected only in mutant S49 cells containing dATP feedback-resistant ribonucleotide reductase and not in wild-type or other mutant S49 cells. (ii) Transfection of Chinese hamster ovary cells with an expression plasmid containing the mutant M1 cDNA resulted in the production of dATP feedback-resistant ribonucleotide reductase. Transfected CHO cells expressing the mutant M1 cDNA exhibited a 15- to 25-fold increase in the frequency of spontaneous mutation to 6-thioguanine resistance, confirming that dATP feedback-resistant ribonucleotide reductase produces a mutator phenotype in mammalian cells. The availability of a cDNA which encodes dATP feedback-resistant subunit M1 thus provides a means of manipulating by transfection the frequency of spontaneous mutation in mammalian cells.